Urgensi Infrastruktur Pendidikan Sebagai Wajah Peradaban Baru Ibu Kota Negara Indonesia Menuju Generasi Emas 2045 - Suhari Muharam (Yayasan Perguruan Kampus, 2023)
The transfer of the capital of the country (IKN) is also a moment for Indonesia to pay more attention to the quality of education in the areas, especially the 3T areas (Front, Remote, and Abandoned), and not let the transfer of IKNs cause educational inequality in the area 3T, just because of too much focus on the development of infrastructure for economic fulfillment. Education plays an important role in producing quality human resources. On that basis, it is vital to reconstruct and reformulate the design of education, especially in the infrastructure aspects, to help realize the golden generation of this nation. The purpose of this research is to provide an overview related to the fulfillment of the educational infrastructure that must be fulfilled in the new IKN. The data collection method used is qualitative-descriptive, with literature studies to describe the meaning and conditions that occur. The results of the study describe the general fluid improvement in the quality of education in Indonesia, which is among the fastest. However, it has not been accompanied by the corruption of education in the territory of Indonesia. To consolidate the educational infrastructure, the government must be able to commit itself to solving the education problem in Indonesia because the government has a primary responsibility for advancing education.